Uji Kesesuaian Kinerja dan Analisis Reproduksibilitas Akurasi Tegangan Tabung Pesawat Sinar-X di Balai Pengamanan Alat Fasilitas Kesehatan Makassar - Nur Isnaeni,; Suci Khusnul Amelia,; M. Ichzan,; Jumardin, Jumardin; Sitti Nurrahmi,; Jasdar Agus,; Dwi Febri Isradianti,; Khaerul Bariah, (JFT: Jurnal Fisika dan Terapannya, 2024)
The X-ray beam collimation test, voltage accuracy test, reproducibility test, and fourth is the X-ray beam output test (Half Value Layer) on the Mobile X-ray aircraft. This testing aims to determine the standards that have been set. Tests that have been carried out on the illumination and the difference between the collimation field of the beam and the X-ray beam show that the results obtained have passed the test on an X-ray aircraft. Both tests are in accordance with established standards. Reproducibility testing is carried out by measuring the radiation output (mGy) at the same settings repeatedly. The data shows a corrected mean of 0.075 mGy with a standard deviation of 0.0034, indicating that the X-ray aircraft has good reproducibility in producing consistent radiation output. The mobile X-ray unit tested had sufficient accuracy and reproducibility that complied with established standards and demonstrated the reliability of the device in clinical practice. X-ray beam output testing was carried out and a corrected HVL value was obtained which was greater than the test pass value. The results obtained are in accordance with established standards.